(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Foreseeing the future is considered a practical skill that involves extrapolating many future trends in human life, which affect, in one way or another, the paths of individuals and societies as a whole. Foresight aims to discover problems and risks before they occur and then prepare for them or prevent them from occurring. It can provide optimal use. A group of future methods has good visions in the banking business environment. Foresight does not mean predicting future events, but rather it is a process and skill whose goal is to gain knowledge and provide sufficient knowledge to achieve the desired future goals. Therefore, adopting the future foresight approach will reduce error, surprise, and surprise in the paths of life, which is the opposite of... chaos and randomness Foresight is a set of activities, skills, preparation for the future, and the development of strategic plans around the challenges and risks that are likely to occur. The research included two axes: the first dealt with the concept of foresight, its methods, principles, and stages. As for the second axis, the Sherrod model was used on the financial statements of the International Development Bank and its reflection on Auditor’s report. The most prominent results reached in this research, according to the opinions of experts, are: the lack of future forecasting procedures and an action plan with clear goals and a specific timetable, and that forecasting helps in identifying obstacles and problems that banks will be exposed to in the future The most prominent recommendations reached by the research are: the necessity of using the Sherrod model to permanently audit future forecast estimates as an early warning of the future condition of the bank sample of the research and benefiting from the results in the auditor’s report.